TOWARDS AN INNOVATION CLUSTER IN INDONESIA - A LITERATURE STUDY AND RESEARCH AGENDA - Dhewanto, Wawan; Sri, Herliana; Ratnaningtyas, Sudrajati; Indra T., Masca (Jurnal Manajemen Teknologi, 2013)
One of the most common topics discussed in the early 90â??s was the emergence of globalised and technologically advanced world. One of the 'measurements' which is very important in determined the country competitiveness in globalization era is their productivity. Developed countries has realise the innovation, diffusion and learning processes are believed as a key success factors to determine their productivity and those three factors gathering together to generate competitive advantage. Therefore, strengthening the innovation system becomes a very important agenda in many countries and coupled with the phenomenon of business agglomeration or the clustering phenomenon that can be seen around the world. While the concepts of clustering have been investigated for the last twenty years, there has been relatively deficiency of research on the issue of innovation cluster, especially in Indonesia. For that purpose, this paper described a literature review in context of innovation and cluster that emerge in the developed countries and how the development cluster and innovation itself in Indonesia. By analyzing the correspond literature, the best standard of innovation cluster are refined and enhanced. The results of this study contribute as a guide for potential areas for future research.